Child language acquisition research on indigenous African sign languages: A commentary on Kidd and Garcia (2022). Issue 6 (December 2022) - Edward, Mary
It is not always the case that an endangered language goes through a revitalisation programme. For most endangered languages, there are no attempts for revitalisation, and we may never hear of them, nor understand their child language acquisition process. Currently, our understanding of sign language acquisition by children is framed by the research on the few sign languages that have child language acquisition research projects. There is a dearth of research on child language acquisition of indigenous African sign languages.